Human hair keratin hydrogel : fabrication, characterization and application - Wang, Shuai (2015)
Human hair keratins are readily available, easy to extract and eco-friendly materials with promising bioactivities. These properties make them the ideal building blocks for a scaffold. This research was aimed at developing keratin-based materials with an emphasis on keratin hydrogels. We started with keratin extraction from human hair. The optimized extraction method yields 24 ±1% soluble proteins from human hair. The major components were keratins and keratin associated proteins. The most abundant amino acids were cysteine (>10 mol %), Glutamine/ Glutamic acid (13.6 mol %) and Proline (11 mol %). The first application was using CaCl2 induced keratin hydrogels as 2D cell culture substrates. The CaCl2 induced keratin hydrogels were first tested for physical and mechanical properties. In the in vitro experiment, L929 cells seeded on keratin hydrogels had an average proliferation rate 76% compared to cells on collagen hydrogels. They were also less elongated and formed localized proliferative cell colonies. The second application was using citrate buffer induced keratin hydrogels as 3D cell culture scaffolds. A new keratin gelation method using citrate buffer was developed. Live cell encapsulation was facilitated by controlling factors such as concentration, pH and temperature. This 3D cell culture system was able to support cell viability and proliferation. Further in vitro/ in vivo preliminary studies of keratin-based material demonstrated promising biocompatibility. Thus this novel keratin hydrogel technique has the potential to be used as either 2D or 3D soft tissue templates.